2017
DOI: 10.18203/2394-6040.ijcmph20174122
|View full text |Cite
|
Sign up to set email alerts
|

A study on the prevalence of dental caries among the school-going children in Tamil Nadu

Abstract: Background: Dental caries is an important social problem in India and is predominantly a disease of childhood. The prevalence and incidence of dental caries is influenced by various socio–demographic factors like age, sex, ethnic groups, dietary patterns and oral hygiene habits. The objective of the study were to estimate the prevalence of dental caries among the school going children aged between 5–10 years and to determine the risk factors associated with dental caries.Methods: A population based cross–secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…Similarly, Gomathi et al, in their study reported slightly higher prevalence among girls (54%) than boys (46%). 2 Mulu et al in their study, found the prevalence of dental caries was higher among girls (24.4%) than that of boys (18.5%) while Khanal et al also observed higher prevalence among girls (62.7%) than that of boys (53.4%). 11,14 The higher dental caries prevalence among girls might be due to early eruption of teeth in girls and hence their teeth being exposed to caries prone environment for a longer duration when compared with boys.…”
Section: Gendermentioning
confidence: 87%
See 4 more Smart Citations
“…Similarly, Gomathi et al, in their study reported slightly higher prevalence among girls (54%) than boys (46%). 2 Mulu et al in their study, found the prevalence of dental caries was higher among girls (24.4%) than that of boys (18.5%) while Khanal et al also observed higher prevalence among girls (62.7%) than that of boys (53.4%). 11,14 The higher dental caries prevalence among girls might be due to early eruption of teeth in girls and hence their teeth being exposed to caries prone environment for a longer duration when compared with boys.…”
Section: Gendermentioning
confidence: 87%
“…1 years children found that the prevalence of dental caries was 65.88%. 2,7,10 Dental caries being a cumulative process showed high prevalence in children mainly due to accessibility to caries prone foods. The higher overall prevalence of caries status indicates continued negligence of oral health.…”
Section: Agementioning
confidence: 99%
See 3 more Smart Citations